Limestone-zeolite biocomposite as potential low-cost adsorbent for landfill leachate remediation - Rosli, Mohd Arif; Daud, Zawawi; Ridzuan, Mohd Baharudin; Awang, Halizah (2020)
A novel approach for the low-cost bioadsorbent for the removal of leachate pollutants is presented herein. In this study, limestone is combined with zeolite in order to fabricate biocomposite media with different ratios. Results revealed that limestone-zeolite biocomposite adsorbed ammoniacal nitrogen (NH3-N) and COD, which could possibly be used for the adsorption of NH3-N and COD efficiently from leachate. The optimum mixing ratio by means was carried out using series of batch experiments for limestone and zeolite to measure the remediation of NH3-N and COD in a stabilized leached. The optimum ratio for limestone and zeolite in the remediation of NH3-N and COD obtained were at 25:15 (82%) and 30:10 (75%), respectively. Indeed, the prepared limestone-zeolite biocomposite is a low-cost and effective adsorbent was potential used to derive the NH3-N and COD for a promising adsorption efficiency from stabilized landfill leachate.